The idea of popular schooling in Upper Canada print culture, public discourse, and the demand for education - Di Mascio, Anthony, 1975- (Montreal [Que.] : McGill-Queen's University Press, 2012)
A study of the popular movement and political agitation for educational reform in Upper Canada.
Between Vision and Impetus: The Deep Roots of Schooling, 1784-1799 -- From Educational Expansion to Educational Deadlock, 1800-1811 -- War and Schooling, 1812-1815 -- The Rise and Fall of Common Schooling in the Postwar Era, 1816-1824 -- Education and the Rise of Radical Political Thought, 1824-1826 -- Ecclesiastical Exclusivity Denounced: Religious Discourse and the Politics of Education, 1826-1828 -- Renewal or Regression? Educational Discourse in a Time of Political Discord, 1828-1830 -- Toward Mass Universal Schooling: Societal Reorganization in the Age of Movable Type, 1830-1832 -- Conclusion.
Includes bibliographical references (p. [205]-235) and index.
Keywords: Education -- Ontario -- History -- 19th century; Education -- Social aspects -- Ontario -- History -- 19th century; Education -- Political aspects -- Ontario -- History -- 19th century; Public schools -- Ontario -- History -- 19th century; Ontario -- Intellectual life -- 19th century; EDUCATION / Comparative; EDUCATION / History; Electronic books